Electrochemically Mediated Synthesis of Cyanated Heterocycles from α‐amino Esters, Pyridine‐2‐carbaldehydes and NH 4 SCN as Cyano Group Source - Grishin, Sergei S.; Ustyuzhanin, Alexander O.; Vil', Vera A.; Terent'ev, Alexander O. (Chemistry : a European journal, 2025)
The electrochemically mediated cyanation/annulation process with in situ cyanide ion generation from NH 4 SCN and multi‐step oxidative construction of CN‐functionalized heterocycles from easily available α‐amino esters and pyridine‐2‐carbaldehydes has been discovered. Depending on the nature of the α‐amino ester, 1‐cyano‐imidazo[1,5‐a]pyridine‐3‐carboxylates, 3‐alkyl‐ and 3‐aryl‐imidazo[1,5‐a]pyridines‐1‐carbonitriles, and the first reported 4‐oxo‐4 H ‐pyrido[1,2‐a]pyrazine‐1‐carbonitriles were obtained. The electrosynthesis is carried out in an undivided electrochemical cell under constant current conditions. The success of the discovered electrochemical synthesis is based on the combination of two anodic processes: oxidation of SCN anion to CN anion and oxidation of C−N bonds to C=N bonds during heterocycle construction. Mechanistic studies based on CV measurements, and control experiments confirm the generation of [CN] species from NH 4 SCN with subsequent addition to an imine formed from α‐amino esters and pyridine‐2‐carbaldehyde. Computational analysis suggests that for reactive intermediates from glycine esters, the subsequent 5‐ endo ‐trig cyclization leading to 1‐cyano‐imidazo[1,5‐a]pyridine‐3‐carboxylates is more favourable and the 6‐ exo ‐trig cyclization leading to 4‐oxo‐4 H ‐pyrido[1,2‐a]pyrazine‐1‐carbonitriles is less favourable. For α‐amino esters with alkyl or aryl substituents, both cyclization pathways are relatively thermodynamically possible. The leading 4‐oxo‐4 H ‐pyrido[1,2‐a]pyrazine‐1‐carbonitrile showed high fungicidal activity against phytopathogenic fungi.